2007
DOI: 10.1016/j.jvs.2006.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Radiation arteritis: A contraindication to carotid stenting?

Abstract: CAS for radiation arteritis has poor long-term anatomic outcome and can present with late asymptomatic occlusions. These findings suggest that these patients require closer postoperative surveillance and raise the question of whether CAS is appropriate for carotid occlusive lesions caused by radiation arteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 27 publications
(35 reference statements)
6
60
2
3
Order By: Relevance
“…In addition, there were significantly fewer patients with CAD, hypertension, hyperlipidemia, DM, and chronic kidney disease in our XRT group, and this finding differed from similar studies reported in the Western literature. [9,10] The perioperative complications and primary outcomes, all causes of mortality, ipsilateral recurrent stroke, and MACE, did not significantly differ between the XRT and non-XRT patients, as noted previously. [9,10] However, a significantly higher restenosis rate was observed in our XRT patients, which correlated with previous studies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, there were significantly fewer patients with CAD, hypertension, hyperlipidemia, DM, and chronic kidney disease in our XRT group, and this finding differed from similar studies reported in the Western literature. [9,10] The perioperative complications and primary outcomes, all causes of mortality, ipsilateral recurrent stroke, and MACE, did not significantly differ between the XRT and non-XRT patients, as noted previously. [9,10] However, a significantly higher restenosis rate was observed in our XRT patients, which correlated with previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…Information regarding such a large number of XRT patients is a unique characteristic of our study when compared to similar studies performed in the West. [9,10] The mean age of our XRT patients was significantly lesser compared to the non-XRT patients. In addition, there were significantly fewer patients with CAD, hypertension, hyperlipidemia, DM, and chronic kidney disease in our XRT group, and this finding differed from similar studies reported in the Western literature.…”
Section: Discussionmentioning
confidence: 77%
“…The incidence of restenosis after CAS has been in the range of 3% to 5%. [215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233] The incidence of TIA has been reported as 1% to 2% in patients undergoing CAS. Intracranial hemorrhage and the hyperperfusion syndrome related to hypertension and anticoagulation have been reported as complications in <1% of CAS procedures.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…The overall 3-year rate of freedom from all fatal and non fatal strokes was 96% [15]. Unfortunately, the long-term clinical durability of stenting for this indication is questioned, since severe in-stent restenosis and occlusion has been reported [16,17]. The routine use of EPDs is advocated with CAS.…”
Section: Revascularization Endarterectomymentioning
confidence: 99%